2018
DOI: 10.1186/s12974-018-1206-5
|View full text |Cite
|
Sign up to set email alerts
|

Abnormalities of age-related T cell senescence in Parkinson’s disease

Abstract: BackgroundA wealth of evidence implicates both central and peripheral immune changes as contributing to the pathogenesis of Parkinson’s disease (PD). It is critical to better understand this aspect of PD given that it is a tractable target for disease-modifying therapy. Age-related changes are known to occur in the immune system (immunosenescence) and might be of particular relevance in PD given that its prevalence rises with increasing age. We therefore sought to investigate this with respect to T cell replic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
50
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 43 publications
8
50
1
Order By: Relevance
“…These observations add to existing evidence suggesting that the association of senescence of blood cells with neurodegenerative diseases might not be as simple as originally thought. In particular, our own previous immuno-phenotyping studies showed a reduction of 'late senescent' CD8+ T cells (identified as CD28 lo CD57 hi ) in PD cases versus controls [62]. Furthermore, in AD patients monocytic p21 protein levels were decreased compared to control individuals [59].…”
Section: Senescence Markersmentioning
confidence: 89%
“…These observations add to existing evidence suggesting that the association of senescence of blood cells with neurodegenerative diseases might not be as simple as originally thought. In particular, our own previous immuno-phenotyping studies showed a reduction of 'late senescent' CD8+ T cells (identified as CD28 lo CD57 hi ) in PD cases versus controls [62]. Furthermore, in AD patients monocytic p21 protein levels were decreased compared to control individuals [59].…”
Section: Senescence Markersmentioning
confidence: 89%
“…Exclusion criteria were: other neurodegenerative disorders, chronic inflammatory or autoimmune disorders, current clinically significant infection or use of anti-inflammatory/immunomodulatory medications, surgery within the last month, or recent vaccinations. Data from this cohort also contributed to our previously published study ( 25 ).…”
Section: Methodsmentioning
confidence: 99%
“…Immune dysfunction has been associated with PD and its progression ( 2 5 ) and represents a tractable target for disease modification. However, the cellular and molecular mechanisms underpinning this association have yet to be elucidated.…”
Section: Introductionmentioning
confidence: 99%